2016
DOI: 10.1111/1744-7917.12361
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild predation and competitive displacement between Nesidiocoris tenuis and Dicyphus maroccanus, two biological control agents in tomato pests

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
1
11
1
1
Order By: Relevance
“…In various crop systems, different zoophytophagous species naturally colonize the plants (Albajes and Alomar, 1999;Montserrat et al, 2000;Alomar et al, 2002). For instance, Dicyphus maroccanus and N. tenuis are both present on tomato plants in eastern Spain (Salas Gervassio et al, 2017). However, N. tenuis tends to displace D. maroccanus from plants because of higher competitive abilities.…”
Section: Interactions With Competitors and Intraguild Predationmentioning
confidence: 99%
“…In various crop systems, different zoophytophagous species naturally colonize the plants (Albajes and Alomar, 1999;Montserrat et al, 2000;Alomar et al, 2002). For instance, Dicyphus maroccanus and N. tenuis are both present on tomato plants in eastern Spain (Salas Gervassio et al, 2017). However, N. tenuis tends to displace D. maroccanus from plants because of higher competitive abilities.…”
Section: Interactions With Competitors and Intraguild Predationmentioning
confidence: 99%
“…The mean survival of N. tenuis was lower than that of D. cerastii or M. pygmaeus nymphs. Salas Gervassio et al (2017) found a different result in the Dicyphus maroccanus Wagner– N. tenuis system; D. maroccanus females preyed on N. tenuis first instars in fewer than 5% of cases, but N. tenuis females killed D. maroccanus first instars in 30% of cases.…”
Section: Discussionmentioning
confidence: 97%
“…Indirect competition can be more important than direct interactions between mirid species. Salas Gervassio et al (2017) reported that N. tenuis can be a better competitor than other species of mirids, describing its greater capacity to obtain food and reach larger population sizes compared to other mirids in eastern Spain tomato crops. Michaelides et al (2017) also found that N. tenuis is a better competitor than M. pygmaeus when feeding on T. absoluta eggs, so it is possible that D. cerastii may also be outcompeted by N. tenuis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Verder moet er rekening mee worden gehouden dat N. tenuis warmte minnend is en bij hogere temperaturen zich nog steeds sneller kan ontwikkelen dan andere soorten. Recent is bij een competitieproef tussen N. tenuis en D. bolivari in tomaat gevonden dat ondanks het negatieve effect van D. bolivari op de ontwikkeling van N. tenuis, de populatiegroei van N. tenuis bij 25°C nog steeds veel groter is dan bij D. bolivari(Salas Gervassio et al 2016).Opvallend was dat in onze studie M. pygmaeus in het laboratorium géén effect had op N. tenuis, zowel met al zonder alternatief voedsel. Dit geeft aan dat deze roofwants minder agressief is dan de andere soorten en is een bevestiging van eerdere studies(Moreno-Ripoll et al 2012).…”
unclassified